Handbook of vacuum technology - Jousten, Karl [ed.] (Weinheim Wiley Vch, 2008)
A comprehensive standard work and important resource for both students and professionals in research and industry who need detailed knowledge of the theory and applications. Many numerical examples and numerous illustrations visualize the theoretical issues, backed by many useful tables and charts, plus over 500 illustrations. The Handbook discusses the latest developments in vacuum measurement techniques and leak detection in vacuum systems, as well as the connection of vacuum systems to computerized control systems.
Translated From The German.
Keywords: Vacuum technology